Aspirin resistance in patients with acute ischemic stroke - ÖZBEN SADIÇ, BESTE (SPRINGER HEIDELBERG, 2011)
Aspirin is used in ischemic stroke therapy. However, some patients are not responsive to the antithrombotic action of aspirin. The aim of this study was to assess the prevalence of aspirin resistance in stroke patients and its association with mortality. One-hundred and six patients (mean age 64.9 +/- A 14.6 years, 53 male) with acute ischemic stroke were consecutively recruited. All subjects were taking aspirin regularly. Aspirin responsiveness was determined by Ultegra Rapid Platelet Function Assay-ASA (VerifyNow Aspirin). Aspirin resistance was defined as aspirin reaction unit (ARU) a parts per thousand yen 550. Aspirin resistance was detected in 35 patients. There were not any significant differences in age, gender and comorbidities between aspirin-resistant and aspirin-sensitive patients. The mean National Institute of Health Stroke Scale (NIHSS) scores of the aspirin-resistant and aspirin-sensitive patients were 15 +/- A 3 and 12 +/- A 5, respectively (p = 0.006). Twenty-seven patients had a history of prior ischemic stroke and eight of them had aspirin resistance. Eleven patients died in-hospital and a total of 43 patients died during 2 years. Both the in-hospital and 2-year mortality rates were significantly higher in patients with aspirin resistance (20 vs. 5.6%, p = 0.038 and 60.0 vs. 31.0%, p = 0.004, respectively). Regression analysis revealed aspirin resistance [odds ratio (OR) 3.097, 95% confidence interval (CI) 1.070-8.959, p = 0.037] as an independent predictor of 2-year mortality, as well as age (OR 1.051, 95% CI 1.003-1.102, p = 0.038) and NIHSS scores (OR 1.208, 95% CI 1.016-1.437, p = 0.033). Aspirin resistance is not uncommon in patients with acute ischemic stroke and is associated with short and long term mortality in these patients.
Keywords: Acute stroke; Aspirin; Aspirin resistance; Ischemic stroke; Mortality; Prognosis; VARIABLE PLATELET RESPONSE; HIGH-RISK PATIENTS; MYOCARDIAL-INFARCTION; OPTICAL AGGREGOMETRY; METABOLIC SYNDROME; DIABETES-MELLITUS; FUNCTION ASSAY; FUNCTION TESTS; DOSE ASPIRIN; DOUBLE-BLIND